Development of PISA-Like Math Tasks for Uncertainty and Data Using the Context of COVID-19 - Kori Auga Islamirta; Ratu Ilma Indra Putri; Hapizah Hapizah; Isri Mawarni (Jurnal Pendidikan Matematika, 2022)
This study aims to produce valid and practical questions and discover the potential effect of PISA-Like Math Tasks on uncertainty and data content using the COVID-19 context on mathematical literacy skills. The subjects of this study were students in Grade 9 of Junior High School number 19 Palembang. The research was conducted using the research design of developmental research. The stages in question development research are the preliminary and formative evaluation stages. The preliminary stage includes analysis of student needs, curriculum analysis, and analysis of PISA evaluation instruments. The formative evaluation stage includes self-evaluation, expert reviews, and one-to-one, small group, and field tests. This study resulted in a set of PISA-Like Math Tasks on uncertainty and data content using the COVID-19 context which consisted of 7 units with 12 valid and practical questions and potential effects on mathematical literacy skills, which included communication skills, reasoning skills, mathematical abilities, representation ability, and strategy selection ability. The resulting PISA-Like Math Tasks can help students think mathematically by using ideas from different subjects to solve a given problem.